Hollywood heroines : women in film noir and the female gothic film - Hanson, Helen (London : I.B. Tauris, 2007)
At the margins of film noir : genre, range and female representation ## Reviewing the female gothic heroine : agency, identification and feminist film criticism ## Narrative journeys of the female gothic heroine ## Men in the woman's film : the gothic male, representation and female discourse ## Professional investigators and femmes fatales in neo-noir ## Reworking the woman's film : the neo-gothic heroine in contemporary cinema ## The currency of Hollywood heroines.
Onderzoek KASK (1KA-OF1001)
boek